MODEL PEMBELAJARAN PENDIDIKAN ISLAM DI ERA MERDEKA BELAJAR (SYSTEMATIC LITERATURE REVIEW) - A’zizah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to examine the role and relevance of the Systematic Literature Review (SLR) method in the context of Islamic education. SLR is a structured and systematic scientific approach used to identify, evaluate, and synthesize relevant research findings on a specific topic or research question. Through this method, researchers can gain in-depth insights into various aspects of Islamic education, including the use of technology in learning, authentic and diagnostic assessment techniques, and the integration of Islamic values into modern curricula. The findings suggest that SLR not only enriches the theoretical foundation but also guides the development of more effective, innovative, and contextual Islamic education practices in the era of Society 5.0. Moreover, SLR serves as a valuable knowledge management tool that contributes strategically to curriculum development, instructional methods, and future research directions. Therefore, this study provides significant contributions for academics, educators, and policymakers in designing relevant and impactful Islamic education strategies.